PERLINDUNGAN DAN PENEGAKAN HAK TENAGA KERJA DALAM HAK ASASI MANUSIA - ARTANA, I WAYAN (Kerta Dyatmika, 2015)
ABSTRACTÂ Freedom is something that is owned by each individual is essential. Rights for workers, as mandated in the UUD 1945, states that every citizen has the right to work and a decent living for humanity. Referring to Law No. 39 In 1999, the government shall be responsible for, protect, uphold and promote human rights in enforcing it includes effective implementation within the scope of human rights law.Related to the workers, the right to privacy includes the right not to be enslaved or be controlled through any of its forms; the right to be free from forced or compulsory labor; the right to freedom of belief, religion and perform their religious beliefs or such; right / association and peaceful assembly; and the right to free speech and or expression.Â Key Words: Workers, Human Rights